Servant Leadership and Organizational Climate on Job Satisfaction: Digital Readiness as a Moderator - Clifford Jeremias Lolang; Susanti Saragih (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2026)
The accelerating pace of digital change requires organizations not only to adopt technology, but also to ensure that their employees are well prepared. To address this issue, this study aims to analyze how servant leadership and organizational climate enhance job satisfaction, in particular how the level of digital readiness influences this relationship. Data were obtained from 147 employees who were actively involved in digital-based work activities, through the distribution of online questionnaires. The hypotheses were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that organizational climate has a positive and significant effect on employee job satisfaction. However, servant leadership does not show a significant effect on job satisfaction in this study’s context. These findings indicate that working with intense digital adoption, employee perception of fulfillment is more influenced by a supportive work climate and the level of digital readiness, rather than by a service-oriented leadership behavior. This study provides some practical implications for managers in developing and promoting practices that support a positive work atmosphere that will lead a higher job satisfaction. In addition, the results also gives an insight for further research to develop a comprehensive model related to work behavior in the digital era.